Bidirectionally Compatible Buffering Layer Enables Highly Stable and Conductive Interface for 4.5 V Sulfide‐Based All‐Solid‐State Lithium Batteries. Issue 32 (26th June 2021) - Wang, Longlong; Sun, Xingwei; Ma, Jun; Chen, Bingbing; Li, Chao; Li, Jiedong; Chang, Liang; Yu, Xinrun; Chan, Ting‐Shan; Hu, Zhiwei; Noked, Malachi; Cui, Guanglei
Abstract: High‐voltage all‐solid‐state lithium batteries (HVASSLBs) are considered attractive systems for portable electronics and electric vehicles, due to their theoretically high energy density and safety. However, realization of HVASSLBs with sulfide solid electrolytes (SEs) is hindered by their limited electrochemical stability, resulting in sluggish interphase dynamics. Here, a bidirectionally compatible buffering layer design scheme is proposed to overcome the interfacial challenges of sulfide‐based HVASSLBs. As a proof of concept, it is found that NASICON‐type Lix Zr2 (PO4 )3 surprisingly exhibit great compatibility with both 4.5 V LiCoO2 and Li6 PS5 Cl, based on the results of first‐principles calculations and various in situ/ex situ characterizations. This compatibility significantly restrains the interface reactivity and boosts interfacial Li‐ion transport. Therefore, 4.5 V sulfide‐based HVASSLBs can exhibit remarkably enhanced initial discharge capacity (143.3 vs 125.9 mAh·g −1 at 0.2C), capacity retention (95.53% vs 74.74% after 100 cycles), and rate performance (97 vs 45 mAh·g −1 at 2C). This work sheds light on the great prospects of sulfide‐based HVASSLBs with high‐rate characteristics, and constitutes a crucial step toward the rational design of interface and interphase chemistry for high‐performance sulfide‐based HVASSLBs. Abstract : A bidirectionally compatible buffering layer design scheme is proposed to overcome the interfacial challenges of sulfide‐based high‐voltage all‐solid‐state lithium batteries (HVASSLBs). As a proof of concept, it is found that NASICON‐type LiZr2 (PO4 )3 exhibits great compatibility with both 4.5 V LiCoO2 and Li6 PS5 Cl, which enables 4.5 V sulfide‐based HVASSLBs with remarkably enhanced initial discharge capacity, capacity retention, and rate performance.